Patterns of teacher-students interaction in eighth grade of junior high school - Rinenda Saka Panjuru (Journal of English Language and Pedagogy, 2019)
The objectives of this research are to: (1) reveal the teacher-students’ interaction patterns applied between teacher and students during teaching and learning process in SMP Muhammadiyah Imogiri., and (2) describe the interactional features used by the teacher related to the pedagogic goals during teaching learning process SMP Muhammadiyah Imogiri. This research belongs to discourse analysis which aims at describing conversation and interaction of teacher-students during English teaching learning process in the eighth grade of SMP Muhammadiyah Imogiri. The data were collected through observation and were analyzed using the theory of IRF exchange structure and the SETT Framework. The result showed there were 30 patterns of interaction of 30 exchange structures used in seven types of transaction. The transactions greeting session, introduction, re-checking session, explaining session, instruction session, practicing session, note taking session. There were 12 types of interactional features used by the teacher with the total number of 135. It appears the display question interactional feature plays an important role in this case. Through display question, the teacher raises up the students’ desire to learn and participate in the teaching learning process. The teacher ‘24’ form-focused on feedback interactional features backs up the students when they did a mistake. That is a good unity to build the students competencies.